Meta-Analysis: The Effectiveness of Zinc on Dhiarrea and Pneumonia in Children Under Five - Anastasia Dwi Anggraeni; Bhisma Murti; Yulia Lanti Retno Dewi (Journal of Epidemiology and Public Health, 2021)
Background: Diarrhea and pneumonia together account for 29% of all child deaths globally, resulting in the deaths of more than two million children each year. Zinc deficiency is associated with decreased immunity and an increase in serious infectious diseases. Zinc deficiency is likely to be a major cause of increased mortality of malnourished infants in developing countries. Numerous studies have shown that zinc supplementation reduces the duration and severity of diarrhea. In addition, zinc administration can also prevent pneumonia, and is effective in recovering fever, shortness of breath and respiratory rate. This study aims to analyze the effectiveness of zinc on the incidence of diarrhea and pneumonia in children under five. Subjects and Method: This research is a systematic review and meta-analysis conducted with PRISMA flow diagram. Article searches through journal databases include: PubMed, Science Direct, and Google Schoolar. The keywords used were (“Zinc” OR “Diarrhea”) AND (“Zinc” OR “Pneumonia”) AND “randomized controlled trial”. Inclusion criteria were full paper articles with Randomized Controlled Trial (RCT) research methods, the relationship measure used was Mean SD and Odds Ratio, the intervention given was zinc, research subjects had an age range of 0-6 years. Eligible articles were analyzed using the Revman5.3 application. Results: Meta-analysis of 14 articles showed that zinc administration reduced diarrhea duration 0.73 days statistically significantly (MD= -0.73; 95% CI-1.22 to -0.24, p<0.003, zinc administration reduced pneumonia duration 0.58 days more rapidly and significantly statistically not significant (MD -0.58; 95% CI-0.32 to -1.04, p<0.001) than placebo. Conclusion: Zinc is effective in reducing the duration of diarrhea and treating pneumonia in children under five.